An exploratory study on the information seeking behavior of litigation lawyers in the National Capital Region - Sipin, Ian Dominic P.
Information seeking is crucial for the work of layers and legal professionals since it involves a great extent of information and knowledge. In the case of litigation lawyers, information is sought to substantiate the arguments to be made in a court or tribunal. The researcher sought to identify the process of litigation lawyers in conducting their research. what sources they use, and if there are circumstances where research may be forgone.